2021
DOI: 10.3389/fsufs.2021.666718
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Biostimulants Formulated With Pseudomonas putida and Clay, Peat, Clay-Peat Binders on Maize Productivity in a Farming Environment in Southern Benin

Abstract: Maize plays a vital role in Benin's agricultural production systems. However, at the producer-level, yields are still low, although the production of this cereal is necessary for food security. The aims of this study were to assess the efficacy of solid biostimulants formulated from the rhizobacteria Pseudomonas putida and different binders on maize cultivation in the farming environment in three (03) study areas in South Benin. For this purpose, three (03) biostimulants were formulated based on Pseudomonas pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…This crop is generally considered sensitive to salt stress because if grown in saline soils or irrigated with inappropriate water, it can show alterations in some physiological and biochemical parameters, germination, and biomass production [20]. Several studies focused on the effect of biostimulants on maize grown under normal conditions, highlighting the effectiveness of the various materials tested on the crop productivity, quality, and yield [21][22][23][24]. Differently, less attention has been paid to the use of biostimulants to increase maize resistance to salinity, even though it has been recently demonstrated that biostimulants can help this crop in contrasting the deleterious effects of salt stress [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…This crop is generally considered sensitive to salt stress because if grown in saline soils or irrigated with inappropriate water, it can show alterations in some physiological and biochemical parameters, germination, and biomass production [20]. Several studies focused on the effect of biostimulants on maize grown under normal conditions, highlighting the effectiveness of the various materials tested on the crop productivity, quality, and yield [21][22][23][24]. Differently, less attention has been paid to the use of biostimulants to increase maize resistance to salinity, even though it has been recently demonstrated that biostimulants can help this crop in contrasting the deleterious effects of salt stress [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study showed that Bacillus inoculation, even in the absence of mineral fertilization, increased phosphorus concentrations in plant roots and shoots compared to fertilized plants. Agbodjato et al (2021) assessed the efficacy of solid biostimulants formulated from the rhizobacteria Pseudomonas FIGURE 5 | Heatmap with cluster analysis. The column corresponds to inoculation concentrations and mineral fertilization doses and the line to the biometric parameters of the maize plant.…”
Section: Discussionmentioning
confidence: 99%
“… Agbodjato et al (2021) assessed the efficacy of solid biostimulants formulated from the rhizobacteria Pseudomonas putida and different binders on maize cultivation in the farming environment. The results obtained show that the best height, stem diameter, and leaf area were obtained by applying biostimulants based on P. putida and half doses of NPK and urea.…”
Section: Discussionmentioning
confidence: 99%
“…Notulae Botanicae Horti Cluj-Napoca Agrobotanici 2 causes pollution due to the use of synthetic products, loss of soil fertility and a decrease in biodiversity, the negative impacts of this activity are now resulting in an irreversible change for the environment (Olivares et al, 2017). New production technologies are needed to reduce the damage caused to our ecosystems and at the same time they are required to be friendly to the environment, these alternatives include the use of biostimulants in agriculture (Agbodjato et al, 2021).…”
Section: Academicpresmentioning
confidence: 99%